Relation between Î±-isoform and phosphatase activity of Na+,K+-ATPase in rat skeletal muscle fiber types - Chaillou, M.; Rigoard, P.; Fares, M.; Francois, C.; Sottejeau, Y.; Maixent, J. M. (Cellular and Molecular Biology, 2011)
In skeletal muscle the relationship between Na+,K+-ATPase activity and isoform content remains controversial (9,6). It could be due to the fiber-type content, membrane isolation and analytical methods. We investigated the distribution of subunit Î±1 and Î±2 Na+,K+-ATPase catalytic isoforms and the Na+,K+-ATPase activity in isolated membranes from white ( type I and glycolitic fibers) and red (type II and oxidative fibers) skeletal muscles. Red Gastrocnemius and White Gastrocnemius muscles were sampled from 8 week-old female Wistar rats and crude membranes were performed. The Na+,K+-ATPase activity and membrane distribution of Na+,K+-ATPase Î±1 and Î±2 isoforms were assessed by ouabain sensitive K-phosphatase (Kpase) measurements and Western Blot respectively. The Na+,K+-ATPase activity was 6 fold lower in White Gastrocnemius membranes than in Red Gastrocnemius membranes. The Î±1 and Î±2-isoform levels are higher in RG than in White Gastrocnemius. The Î±1 and Î±2-subunit Red Gastrocnemius content was significantly higher than in WG. The correlation between crude membrane Kpase activity and both catalytic Î±-subunit of the Na+,K+-ATPase exist.These data suggest that the Na+,K+-ATPase phosphatase activity correlates with the Î±1 and Î±2 isoforms levels in Red Gastrocnemius and White Gastrocnemius and confirms the fiber-specific Na+,K+-ATPase catalytic Î±-subunits and Î±2-isoform as the major catalytic isoform in rat skeletal muscle.